PROTOTYPE OF SHEPAT DRONE BASED ON BOMB FIXEDWING - Nur Rachman Supadmana Muda (International Journal of Social Science, 2025)
The rapid development of drone technology has led to innovations in various fields, including surveillance, security, and transportation. One of the latest advancements is the Shepat Drone prototype, designed based on the aerodynamics of the bomb fixed-wing concept. This study aims to develop a drone that adopts the flight mechanics and stability characteristics of a bomb fixed-wing system, which is known for its high maneuverability and energy efficiency. The methodology involves aerodynamic analysis, biomimetic-based structural design, and performance testing through simulations and direct experiments. The results indicate that the Shepat Drone prototype exhibits better stability in various environmental conditions and higher energy efficiency compared to conventional rotary-wing drones. With this approach, the Shepat Drone has the potential for applications in search and rescue, environmental monitoring, military operations, and industrial use.